Familial Mediterranean Fever: Recent Developments in Pathogenesis and New Recommendations for Management - Özen, Seza; Batu, Ezgi Deniz; Demir, Selcan (Frontiers in Immunology, 2017)
Familial Mediterranean fever (FMF) is the most common monogenic autoinflammatory disease affecting mainly the ethnic groups originating from Mediterranean basin. The disease is characterized by self-limited inflammatory attacks of fever and polyserositis along with elevated acute phase reactants. FMF is inherited autosomal recessively; however, a significant proportion of heterozygotes also express the phenotype. FMF is caused by mutations in the MEFV gene coding for pyrin which is a component of inflammasome functioning in inflammatory response and production of interleukin 1β (IL-1β). Recent studies have shown that pyrin recognizes bacterial modifications in Rho GTPases which results in inflammasome activation and increase in IL-1β. Pyrin does not directly recognize Rho modification, but probably affected by Rho effector kinase which is a downstream event in the actin cytoskeleton pathway. Recently an international group of experts have published the recommendations for the management of FMF. Colchicine is the mainstay of FMF treatment and its regular use prevents attacks and controls subclinical inflammation in the majority of patients. Furthermore, it decreases the long-term risk of amyloidosis. However, a minority of FMF patients fail to response or tolerate colchicine treatment. Anti-IL-1 drugs could be considered in these patients. One should keep in mind the possibility of non-compliance in colchicine-nonresponders. Although FMF is a relatively well-described autoinflammatory disease and almost 20 years has passed since the discovery of the MEFV gene, there are still a number of unsolved problems about it such as the exact mechanism of the disease, symptomatic heterozygotes and their treatment, and the optimal management of colchicine-resistance.